Low Noise C-Band EDFA/DRA Hybrid Amplifier Using the Same Pump Laser - Azawe, Muzahim Ibrahim (Photonics Letters of Poland, 2011)
This paper presents the investigation of a hybrid amplifier consisting of Erbium doped fiber amplifiers EDFAs and a distributed Raman amplifier in the C-band. Our simulations take into account all the effects associated with transmitted signals and a pump laser in the optical fiber. The overall noise figure for the proposed hybrid amplifier was less than 10dB, as a limiting case for maximizing the span length and/or minimizing the impairments of fiber nonlinearities. The combination distributed Raman amplifier and EDFAs present better performance than conventional EDFA-only systems. This low noise figure will enable maximum transmission distance. The transmission is discussed of 16 channels spaced 1nm and 1mW of optical power through 100km of fiber. Full Text: PDF References S.K. Kim, S.H. Chang, J.S. Han, M.J. Chu,"Design of hybrid optical amplifiers for high capacity optical transmission", Electron. Telecom. Res. Inst. J. 24, 81 (2002) T.N. Nielson,"Raman Amplifiers in WDM Systems", 12th LEOS Annual Meeting, vol. 2, 471 (1999) T. Suzuki, M. Kakui, M. Hirano, M. Onishi, Y. Nakai, M. Nishimura,"Broadband discrete fiber Raman amplifier with high differential gain operating over 1.65 /spl mu/m-band", Optical Fiber Comm. Conf. MA3 (2001) S. Kawai, H. Masuda, K. Suzuki, K. Aida,"Wide-bandwidth and long-distance WDM transmission using highly gain-flattened hybrid amplifier", IEEE Photon. Technol. Lett. 11, 886 (1999)[CrossRef] W.Y. Oh, S.S. Lee, H. Lee, W. Seo,"16-Channel C-Band Hy-brid Fiber Amplifier Comprising an EDFA and a Single Diode Laser Pumped Dispersion Compensating Raman Amplifier", European Conf. on Comm. 4.4.5, (2000) H. Suzuki, J. Kani, H. Masuda, N. Takachio, K. Iwatsuki, Y. Tada, M. Sumida,"1-Tb/s (100×10 Gb/s) super-dense WDM transmission with 25-GHz channel spacing in the zero-dispersion region employing distributed Raman amplification technology", IEEE Photon. Technol. Lett. 12, 903(2000)[CrossRef] Y. Zhu, W.S. Lee, C. Scahill, C. Fludger, D. Wetly, M. Jones, J. Homan, B. Shaw, A. Hadjifotiou,"1.28 Tbit/s (32×40 Gbit/s) transmission over 1000 km NDSF employing distributed Raman amplification and active gain flattening", Electron. Lett. 33, 43(2001)[CrossRef] B. Zhu, P.B. Hansen, L. Leng, S. Stulz, T.N. Nielsen, C. Doerr, A.J. Stentz, D.S. Vengsarkar, Z.J. Chen, D.W. Peckham, L. Gruner-Nielsen,"800 Gbit/s (80×10.66 Gbit/s) transmission over 3200 km of non-zero dispersion shifted fibre with 100 km amplified spans employing distributed Raman amplification", Electron. Lett. 36, 1860 (2000)[CrossRef] H. Masuda, S. Kawai, K.-I Suzuki,"Optical SNR enhanced amplification in long-distance recirculating-loop WDM transmission experiment using 1580 nm band hybrid amplifier", Electron. Lett. 35, 411 (1999)[CrossRef] D.A. Chestnut, C. J. S. de Matos, J.R. Taylor,"Raman-assisted fiber optical parametric amplifier and wavelength converter in highly nonlinear fiber", J. Opt. Soc. Am. B- 19, 1901 (2002)[CrossRef] A. Carena, V. Curri, P. Poggiolini,"On the optimization of hybrid Raman/erbium-doped fiber amplifiers", IEEE Photon. Technol. Lett. 13, 1170 (2001)[CrossRef] G.E. Tudury, J. Hu, B.S. Marks, A.S. Lenihan, C.R. Menuk, G.M. Carter,"Gain characteristics of a 210 km hybrid Raman/erbium-doped fiber amplified loop", Opt. Comm. 264, 152 (2006)[CrossRef] H. Masuda, Raman Amplifiers for Telecommunications 2, Sub-Systems and Systems (New York, Springer-Verlag 2004) A.W. Naji, B.A. Hamida, X.S. Cheng, M.A. Mahdi, S. Harun, S. Khan, W.F. AL-Khateeb, A.A. Zaidan, B.B. Zaidan, H. Ahmad,"Review of Erbium-doped fiber amplifier", Int. J. Phys.Scien. 6(20), 4674 (2011) A. Sano, T. Kobayashi, E. Yoshida, Y. Miyamoto,"Ultra-high capacity optical transmission technologies for 100 Tbit/s optical transport networks", IEICE Trans. Commun. E94-B (2), 400 (2011)